Lifestyles of the residents of the Quebrada “La Paja” community, Ecuador - Alcívar, Lisa M.; Briones, Juriana N.; Mendoza, Junior A.; Reyes, Ana C.; Castillo, Driannet; Mendoza, Manuel A. (Revista Gregoriana de Ciencias de la Salud, 2025)
The study examines the lifestyles of Ecuador’s Quebrada “La Paja” community inhabitants, highlighting their impact on health. It is established that lifestyles are crucial to quality of life and that an unbalanced diet and sedentary lifestyle can lead to chronic diseases. The methodology included surveys of 113 people in the community, spanning various ages and genders, to assess their dietary habits and physical activity levels. The results revealed that although most respondents were active through daily work and recreational activities such as soccer, there was also a high consumption of television as a form of leisure, which could contribute to sedentary lifestyles. It is concluded that, despite regular physical activity, the community faces health risks due to inadequate eating habits and a lack of awareness about the importance of a healthy lifestyle, highlighting the need for educational and public health interventions.